Foreign body in urinary bladder: our experience and review of literature - Shafique Ahmed, Mohd Hamid; Pawar, Prakash W.; Sawant, Ajit S.; Sakharani, Jitendra; Arora, Amandeep; Patil, Sunil R.; Patel, Deepak (International Surgery Journal, 2019)
Background: The objective of the study was to study clinical presentation, mode of insertion, and management of intravesical foreign bodies in patients treated at our hospital. Methods: This was a retrospective study conducted between January 2018 to June 2019. Six patients underwent treatment for urinary bladder foreign body at Lokmanya Tilak Municipal Medical College and Sion Hospital, Mumbai, Maharashtra, India. Medical records were analyzed retrospectively with regard to nature of foreign body, each patient’s clinical presentation, the mode of insertion and how the foreign was managed. Results: A total of six foreign bodies were retrieved from patients’ urinary bladders. The patients range in age from 28 to 65 years (mean age was 45 years). The Clinical presentation includes Lower urinary tract symptoms. Four patients were male and two were female. Circumstance of insertion was iatrogenic in 5 patients and self-insertion in 1 patient. Five patients were treated endoscopically (cystoscopy retrieval with or without cystolithotrity) and one patient with supra pubic cystostomy. Post-operative hospital stay was of 1 to 2 days. Mean follow up period was 3 months. Psychiatric referral and counseling were done in patients with history of self-insertion of foreign body in urinary bladder. Conclusions: Foreign body in the urinary bladder remain a challenge to the urologist. Removal of the foreign body without injury to the urinary bladder or the urethra gives good outcome.